2021
DOI: 10.1097/j.pain.0000000000002525
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and treatment of neuropathic pain diagnoses among U.S. nursing home residents

Abstract: Supplemental Digital Content is Available in the Text. The prevalence of pain among nursing home residents who are not receiving analgesics or adjuvants suggests a need to improve pain diagnosis and management procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
(81 reference statements)
0
11
1
Order By: Relevance
“…Concerning neuropathic pain, this study revealed that CPSP (chronic post-stroke pain) was the dominant and the fourth most prevalent principal chronic pain condition overall. This is contrary to a large study from US nursing homes 28 that reports peripheral types of neuropathic pain, like polyneuropathies, but not the central ones. However, we found one study that specifically investigated neuropathic pain in nursing home residents reporting CPSP.…”
Section: Discussioncontrasting
confidence: 99%
“…Concerning neuropathic pain, this study revealed that CPSP (chronic post-stroke pain) was the dominant and the fourth most prevalent principal chronic pain condition overall. This is contrary to a large study from US nursing homes 28 that reports peripheral types of neuropathic pain, like polyneuropathies, but not the central ones. However, we found one study that specifically investigated neuropathic pain in nursing home residents reporting CPSP.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, we did not directly examine the pain subtypes associated with antiepileptic use among NH residents with ADRD, which would enhance our findings. For example, a recently published study found that nearly 15% of NH residents nationwide had a neuropathy diagnosis, and that nearly half of those residents had an antiepileptic prescription fill, primarily gabapentin 31 . However, researchers note that pain subtypes can be underreported in administrative data, at least compared to self‐reports, and that there are low rates of sensitivity for some diagnoses, including neuropathy 32–34 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recently published study found that nearly 15% of NH residents nationwide had a neuropathy diagnosis, and that nearly half of those residents had an antiepileptic prescription fill, primarily gabapentin. 31 However, researchers note that pain subtypes can be underreported in administrative data, at least compared to self-reports, and that there are low rates of sensitivity for some diagnoses, including neuropathy. [32][33][34] Other methods of inquiry, including qualitative work and chart reviews, along with more claims-based analyses would help gain insights into the clinical decisions that are driving these trends.…”
Section: Discussionmentioning
confidence: 99%
“…This may be particularly true of institutionalized older adults, who often experience self-report incapacities. 27 Taken together, these issues may contribute to problems diagnosing neuropathic pain outside of specialty settings. Moreover, the modest to moderate benefit of conventional analgesics for neuropathic pain may factor into treatment uncertainties among HCPs and lack of pain relief among patients.…”
Section: Discussionmentioning
confidence: 99%